2020
DOI: 10.1111/jbi.13791
|View full text |Cite
|
Sign up to set email alerts
|

Plant type dominates fine‐root C:N:P stoichiometry across China: A meta‐analysis

Abstract: Aim Fine roots play an important role in biogeochemical cycling in terrestrial ecosystems. However, our understanding of large scale biogeographical patterns and drivers of fine‐root C:N:P stoichiometry is extremely limited. Location China. Methods We compiled data for fine‐root carbon (C), nitrogen (N) and phosphorus (P) concentrations at 165 sites across China to explore large‐scale biogeographical patterns and drivers of fine‐root C:N:P stoichiometry. Results The geometric means of fine‐root C, N, and P con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 70 publications
2
22
1
Order By: Relevance
“…This result was also in agreement with previous studies that highlighted that the variability and seasonality of temperature and precipitation are the main determinants of root length density (Padilla et al, 2015), RD/length and root branching ratio (McCormack et al, 2020). It is worth noticing that after considering climate variability and seasonality variables, the explanatory power of the environmental component increased by approximately 20% for root chemical traits (compared to the results of Wang et al, 2020) and 25% for SRL and RTD (compared to the results of Wang et al, 2018). This may be related to the fact that these climate variables reflect seasonal fluctuations and variability in temperature and precipitation (Vazquez et al, 2017), which may alter soil nutrient mobility and availability (Morillas et al, 2013;Yang et al, 2020), and thus affect root resource acquisition strategies.…”
Section: Effects Of Climate Variability and Seasonality On Root Traitssupporting
confidence: 92%
See 4 more Smart Citations
“…This result was also in agreement with previous studies that highlighted that the variability and seasonality of temperature and precipitation are the main determinants of root length density (Padilla et al, 2015), RD/length and root branching ratio (McCormack et al, 2020). It is worth noticing that after considering climate variability and seasonality variables, the explanatory power of the environmental component increased by approximately 20% for root chemical traits (compared to the results of Wang et al, 2020) and 25% for SRL and RTD (compared to the results of Wang et al, 2018). This may be related to the fact that these climate variables reflect seasonal fluctuations and variability in temperature and precipitation (Vazquez et al, 2017), which may alter soil nutrient mobility and availability (Morillas et al, 2013;Yang et al, 2020), and thus affect root resource acquisition strategies.…”
Section: Effects Of Climate Variability and Seasonality On Root Traitssupporting
confidence: 92%
“…Kramer‐Walter et al (2016) revealed significant correlations between SRL and soil fertility at a regional scale, but this was not found at a local scale. Wang et al (2020) demonstrated that fine‐root N and P concentrations in all biomes in China were higher than those reported by Zhang et al (2018), who only focused on forest ecosystems in China. Together, these studies suggested that the generalisation of patterns and drivers of root trait variation among different spatial scales is still highly debatable.…”
Section: Introductionmentioning
confidence: 86%
See 3 more Smart Citations